Islamic Religious Education Marketing Service Program as a Strategy for Increasing School Interest at MAN 1 OKU Selatan - Leli Yana; Zainal Berlian; Ahmad Zainuri (The Future of Education Journal, 2024)
Research aims to explain the Islamic Education marketing program to attract public interest so that many prospective new students are interested in entering school at MAN 1 OKU Selatan. This research uses a qualitative approach using narrative research. Islamic religious education has a strategic role in building the character of the younger generation who are faithful, devout and have noble morals. MAN 1 OKU Selatan as an Islamic-based educational institution designed an Islamic religious education marketing services program to promote Islamic values ​​and the superiority of madrasas to the community. This program involves various approaches, such as roadshows to the community, creating digital da'wah content, Islamic communication training, and other supporting activities. The main objectives of this program are to increase public awareness of the importance of religion-based education, expand the accessibility of madrasas, and strengthen the image of madrasas as a superior choice in the education system. With effective implementation, this program has not only succeeded in increasing public interest in Islamic education, but also contributed to strengthening students' character and expanding da'wah to the surrounding environment.